Long-term simulation of potentially toxic elements (PTEs) accumulation and breakthrough in infiltration-based stormwater management practices (SMPs) - Behbahani, Ali; Ryan, Robert J.; McKenzie, Erica R. (Journal of contaminant hydrology, 2020)
Stormwater management practices (SMPs) rely on infiltration and adsorption capabilities of soil and vegetative cover to mitigate the harmful impacts of contaminants in stormwater runoff, including potentially toxic elements (PTEs). Under chemical equilibrium conditions, the soil-water distribution coefficient (Kd) quantifies the relationship between the solid and aqueous phase PTE concentrations, and thus the PTE removal efficiency and mobility through the SMP soil layers during the infiltration process. The SMP loading ratio (LR), the ratio of the drainage area to the SMP infiltration area, combined with runoff concentration determines SMP mass loading and is also expected to impact PTE transport. In this study, a simulation model was developed to investigate PTE breakthrough and build-up in SMP media, considering the impacts of Kd and LR. Eight PTEs were simulated (Cl−, Cr, Fe, Zn, Cu, As, Cd, and Pb), and Cl− was the only PTE that showed high mobility and reached the groundwater table (e.g., ~ 1 year for breakthrough). Conversely, other PTEs were effectively immobilized in the top ~60 cm of soil for a simulated lifespan of 20 years. Soil and porewater contaminant indices, as indicators of SMP lifespan, were estimated based on the ratio of PTE porewater and soil concentrations after 20 years to published standards, suggesting the following order of environmental significance (most concern to least): Cl− > Cr > As > Pb > Fe > Cu > Cd > Zn. After 20 years of simulated use, only Cl− pore water concentrations at the groundwater table exceeded regulatory values, with porewater contamination index values of 4 to 7.5. Chloride also exceeded the surficial media soil contamination index, as did As and Cr, though these exceedences were largely associated with media background concentrations. Generally, higher LR and Kd contributed to higher accumulation of PTEs in top layers; however, simulations showed that the combination of low LR and high Kd may result in lower PTE accumulation in the media, such that the PTE concentration in soil may decrease in deeper layers. In these scenarios, a notable fraction of PTE load was adsorbed on top layers and considerably lower PTE concentrations reached the lower layers. Sensitivity analysis revealed that dispersion, infiltration rate, and kinetically-limited sorption did not impact the PTE accumulation and mobility to a practical extent. The results from this simulation may be adapted to various environmental conditions to enhance the design and maintenance of SMPs. •PTE transport and accumulation in SMPs were simulated to evaluate behavior over a 20-year use case.•Chloride rapidly broke through the media and exceeded regulatory values for soil and drinking water.•PTEs transport is a slow process, and ranked concern: Cl−> Cr > As > Pb > Fe > Cu > Cd > Zn.•Loading ratio and Kd effects can be simultaneously assessed and it is customizable for other locations.•Media background concentrations can lead to problems, so media selection is important.